Preservation of foods - Ingman, Ada (My University, 1898)
Introduction: The preservation of articles of food against decay, and a change in digestibility at the same time is a matter of no small importance, and we were considerably surprised to find that comparatively little attention has been paid to the relative hygienic valve of the various methods of food preservation. The above subject being a wide one, however, it was thought best to limit the discussion, as far as possible, to the effectiveness of the various methods, considered from a hygienic stand-point, describing the methods themselves only when essential to clearness, and using by way of illustration only representative foods. Decay of food takes place by the growth of living germs, from experiment and observation, it is proven that three concurrent conditions are necessary to active putrefaction; the presence of plenty of moisture, exposure to the air and a favorable temperature. The various methods of preservation therefore aim to make conditions unfavorable for the growth of the germs by depriving the foods of their moisture; by lowering the temperature; and by excluding the food from the air or they aim to destroy the germs and ferments by the agency of some chemical compound or germicide.
Citation: Ingman, Ada. Preservation of foods. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Preservation; Food; Digestibility; Representative Foods; Germicide; Theses; Manuscripts (documents)